Flavour encapsulation: A comparative analysis of relevant techniques, physiochemical characterisation, stability, and food applications - English, Marcia; Okagu, Ogadimma Desmond; Stephens, Kristen; Goertzen, Alex; Udenigwe, Chibuike C. (Frontiers in Nutrition, 2023)
Flavour is an important component that impacts the quality and acceptability of new functional foods. However, most flavour substances are low molecular mass volatile compounds, and direct handling and control during processing and storage are made difficult due to susceptibility to evaporation, and poor stability in the presence of air, light, moisture and heat. Encapsulation in the form of micro and nano technology has been used to address this challenge, thereby promoting easier handling during processing and storage. Improved stability is achieved by trapping the active or core flavour substances in matrices that are referred to as wall or carrier materials. The latter serve as physical barriers that protect the flavour substances, and the interactions between carrier materials and flavour substances has been the focus of many studies. Moreover, recent evidence also suggests that enhanced bioavailability of flavour substances and their targeted delivery can be achieved by nanoencapsulation compared to microencapsulation due to smaller particle or droplet sizes. The objective of this paper is to review several relevant aspects of physical-mechanical and physicochemical techniques employed to stabilize flavour substances by encapsulation. A comparative analysis of the physiochemical characterization of encapsulates (particle size, surface morphology and rheology) and the main factors that impact the stability of encapsulated flavour substances will also be presented. Food applications as well as opportunities for future research are also highlighted.